Charcot neuroarthropathy in patients with Charcot Marie Tooth Disease. Issue 8 (December 2021) - Singh, Dishan; Gray, Julia; Laura, Matilde; Reilly, Mary M.
Highlights: Patients who have Charcot Marie Tooth disease are at risk of developing a Charcot neuroarthropathic joint. This is so even in the more common CMT1A where the patient may not complain of sensory deficits, though noticeable on clinical examination. Patients should probably be warned of this risk even if it is relatively rare. It may be advisable to perform joint-preserving procedures rather than arthrodeses in patients with CMT. A tight Achilles tendon may need to be addressed. Consideration should be given to a prolonged period of protective weightbearing after arthrodeses. Abstract: Charcot Marie Tooth disease (CMT) is the most common inherited neuropathy and is also called Hereditary Motor Sensory Neuropathy (HMSN). Whilst both motor and sensory deficits are present, motor deficits tend to predominate over sensory deficits. Charcot neuroarthropathic joints occur in conditions, most commonly diabetes nowadays, where joints are destroyed in association with reduced protective sensation, pain in particular. Three cases of development of Charcot joint disorders in patients with CMT are discussed and the literature is reviewed. Orthopaedic surgeons should be aware that Charcot joints can occur in CMT and surgery can be complicated by Charcot joints.